Meningkatkan Kualitas Hidup Pasien Jantung Melalui Program Rehabilitasi Jantung - Fithriany; Nurhayati; Nurnarita Laila (Bansigom Na Publisher, 2025)
Cardiovascular disease is one of the leading causes of death worldwide, including in Indonesia. Cardiac rehabilitation is a multidisciplinary approach aimed at improving the quality of life of patients with heart disease through a structured program that includes physical activity, health education, psychological support, and lifestyle changes. This study aims to evaluate the impact of a cardiac rehabilitation program on improving the quality of life of heart disease patients in Indonesia. The cardiac rehabilitation program consists of physical exercises tailored to the patients' condition, counseling on stress management, and education on healthy eating habits and the importance of smoking cessation. The research method used is a quantitative approach with a pre-post test experimental design, involving 50 heart patients who participated in the rehabilitation program for 12 weeks. The results showed a significant improvement in the quality of life of patients, measured in terms of physical, emotional, and social aspects, after undergoing the rehabilitation program. Additionally, patients experienced a reduction in anxiety and depression levels, as well as an improvement in physical fitness, which positively impacted their heart health. These findings emphasize the importance of cardiac rehabilitation programs as an integral part of post-treatment care for heart disease patients, which can enhance their quality of life and reduce the risk of further complications.